Cselédek 2
cook from Lesencetomaj, hard work, poor meals, archival document of a work book, Csákvár, strike for higher pay, excerpts from theatre recording, butler from Szigetszentmárton, valet, escaping bad master, controlled by gendarmerie, beating, housemaid, prior to 1945, new type of servants, cleaning women of the party headquarters and for Károly Grósz Gyula Sághy